Eﬀect of structured physical therapy program on patients with diabetes and mild cognitive impairment: randomised controlled trial - Sewillam, Asmaa E.; Hasan Sry, Zahra M.; Salem, Naguib A.; Ahmed Hussein, Ayat Allah Farouk; Essmat, Ahmed; Ali Abdeen, Heba Ahmed (Wydawnictwo Akademii Wychowania Fizycznego im. Polskich Olimpijczyków we Wrocławiu, 2024)
Introduction. The mild cognitive impairment (MCI) refers to a condition that falls in between dementia and the normal cognitive ageing process. Aim of the study: to explore how a physical therapy rehabilitation program aﬀected patients with type 2 dia-betes mellitus (T2DM) and MCI.Methods. The study included 37 elderly patients with T2DM and MCI from Al-Azhar University Hospital aged from 60 to 75 years old. After a physician’s referral, they were randomly allocated into two groups. Group A: 27 patients, underwent a three-session per week, 60-minute physical therapy rehabilitation program in addition to medical treatment. The twelve-week program also included resistive exercise, stretching exercises, and aerobic treadmill walking. The 10 patients in Group B only received medical treatment for a total of twelve weeks. Researchers assessed Glycosylated haemoglobin (HbA1c), the p300 neurophysiological test, Mini-Mental State Examination (MMSE) scale, and Montreal Cognitive Assessment (MOCA).Results. There were signiﬁcantly decreased HbA1c and P300 post-treatment compared to pre-treatment within the study group (p = 0.0001 and p = 0.0001, respectively) and control group (p = 0.005 and p = 0.0001, respectively). The MOCA signiﬁcantly increased post-treatment compared to pre-treatment within the study group, but there was no signiﬁcant diﬀerence in the MOCA between pre- and post-treatment in the control group. The study group had decreased HbA1c, and increased MMS, MOCA, and P300 (13.72, 19.34, 18.7, and 7.2%, respectively) compared to the control group (11.06, 11.06, 9.3, 5.98%, respectively).Conclusions. Physical therapy rehabilitation programs are important in helping patients with T2DM for improving their memory and cognitive function as well as decreasing the MCI progression.
Keywords: diabetes mellitus; cognitive dysfunction; rehabilitation program; mental status and dementia tests